The Different Strategies used for the Early Diagnosis of Alzheimer’s Disease - Sandeep, C. S.; Sukesh Kumar, A. (Asian Journal of Engineering and Applied Technology, 2019)
Gerontology or the scientific study of old age deal with the many clinical problems that are common in the elderly population and many of these follow the orthodox pattern of clinical practice. Patients characteristically have poor insight and often attribute their early symptoms of amnesia to normal aging. Alzheimer’s disease (AD) is a common form of senile dementia that makes disabilities in cognitive behavior and performs routine functions. There are several causes for the disease. Although our understanding of the key steps underlying neurodegeneration in Alzheimer’s disease (AD) is incomplete, it is clear that it begins long before symptoms are noticed by the patient. The aim of this paper is to give an overall idea of the hallmarks, stages of the disease, signs or symptoms and the different methods used for its diagnosis. Any disease-modifying treatments which are developed are most likely to be successful if initiated early in the process, and this requires that we develop reliable, validated and economical ways to diagnose Alzheimer’s−type pathology. However, despite comprehensive searches, no single test has shown adequate sensitivity and specificity, and it is likely that a combination will be needed. There are several clinical tests and neuroimaging techniques used in clinical practice for the diagnosis of Alzheimer’s – type pathology. Prominent of them are biomarkers, Magnetic Resonance Imaging Scan (MRI), Positron Emission Tomography (PET) and Single−Proton CT Scanning (SPECT). Using the new advanced Biomedical Engineering Technologies to the clinical practices stated above, we can develop a computer-aided tool for the early diagnosis of AD. The different soft computing tools in Biomedical Engineering for developing a computer-aided tool are Neural Networks, Genetic algorithm, Wavelet Networks, Support Vector Machines, and Fuzzy Logic. In this paper, we have focused on the different causes as well as the different strategies used for the early diagnosis of Alzheimer’s disease (AD).